Алгебра. Даю 16 б.
2. Упростите выражение:
1) a) (2a-b)(2a+b)+b2;
б) (x + 7)2- 10x;
2) a) (a -c)(a+c)-(a -2c)2;
б) 9x2-(c+3x)(c-3x);
г) 5b" - (a - 2b)";
б) (x+ 3)2 - (x-3)2;
b) (a + 3c)' + (b + 3c)(b - 3c);
г) (x-4y)' +(x+4y)";
д) (x-3)(х+ 3)-(x+8)(x-8);
e) (2a + 1)(2a - 1) + (a - 7)(a + 7).
Answers & Comments
Ответ:
1)
a) (2a-b) (2a+b) + b^2 = 4a^2
б) (x+7)^2-10x= x^2+4x+49
в) 9x^2-(c+3x)=18x^2-c^2
г) 5b^2-(a-2b)^2=b^2-a^2+4ab
2)
a) (a-c) (a+c)-(a-2c)^2= -5c^2+4ac
б) (x+3)^2-(x-3)^2=2x^2+32y^2
в) (a+3c)^2+(b+3c) (b-3c)=a^2+6ca+b^2
г)(x-4y)^2+(x+4y)^2=2x^2+32y^2
д)(x-3) (x+3)-(x+8) (x-8)=55
е)(2a+1) (2a-1)+(a-7) (a+7)=5a^2-50